Hyperthyroidism in the pregnant woman: Maternal and fetal aspects - Mariacarla Moleti; Maria Di Mauro; Giacomo Sturniolo; Marco Russo; Francesco Vermiglio (Journal of Clinical & Translational Endocrinology, 2019)
Hyperthyroidism during pregnancy is uncommon. Nonetheless, prompt identification and adequate management of hyperthyroidism in a pregnant woman is essential, because uncontrolled thyrotoxicosis significantly increases the risk of maternal and fetal complications. Also, fetal prognosis may be affected by the transplacental passage of maternal thyroid stimulating antibodies or thyrostatic agents, both of which may disrupt fetal thyroid function. Birth defects have been reported in association with the use of antithyroid drugs during early pregnancy. Although rarely, offspring of mothers with Graves’ disease may develop fetal/neonatal hyperthyroidism, the management of which requires a close collaboration between endocrinologists, obstetricians, and neonatologists.Because of the above considerations, the management of pregnant and lactating women with hyperthyroidism requires special care, bearing in mind that both maternal thyroid excess per se and related treatments may adversely affect the newborn’s health.In this review we discuss the diagnosis and management of hyperthyroidism in pregnancy, along with the impact of thyrotoxicosis and medications on fetal outcome. Keywords: Pregnancy, Hyperthyroidism, Thyrotoxicosis, Gestational transient thyrotoxicosis, Graves’ disease